An Examination of Student Loans, Partisanship and Complaining Behavior: The Consumer Financial Protection Bureau - Cho, Jihoon; Krush, Michael T.; Walker, Doug; Nowlin, Edward L. (My University, 2022)
This research examines consumer complaints within a government-to-consumer context. The study is focused on two highly discussed topics, student loans and partisanship. While student loans are widely promoted to college students, outstanding U.S. student loan debt trails only consumer debt. Similarly, a stark contrast exists between the views of the two major political parties within the U.S. Our examination provides a nuanced view of partisanship and its effect on complaining behaviors within the student loan realm. Specifically, our study investigates whether partisanship affects the level of student loan complaints submitted to a federal agency initiated during partisan division. Our contributions include the use of a diverse, integrated database that enables insights into complaining behaviors within an understudied area, the government-to-consumer context.
Keywords: Complaints; Partisanship; Student loans; CFPB